Factors affecting taxpayer compliance: understanding of tax accounting, quality of fiscal services, tax sanctions - Marlina, Leni; Kuntadi, Cris (Gema Wiralodra, 2023)
Literature review article on the influence of understanding of tax accounting, quality of tax administration services, and tax sanctions on taxpayer compliance. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The method of writing this article is to use the library research method whose sources come from online media, including Google Scholar, Mendeley and other academic online media . The results of this literature review article are as follows: 1) understanding of accounting affects taxpayer compliance; 2) the quality of tax authorities' services affects taxpayer compliance; and 3) Tax sanctions affect taxpayer compliance.